2008
DOI: 10.1111/j.1423-0410.2008.01093.x
|View full text |Cite
|
Sign up to set email alerts
|

Acquired Glanzmann's thrombasthenia caused by glycoprotein IIb/IIIa autoantibodies of the immunoglobulin G1 (IgG1), IgG2 or IgG4 subclass: a study in six cases

Abstract: Although it might be a rare event, one should be aware of acquired GT as a cause of an unexpected primary disorder of haemostasis in patients with lymphoma or autoimmune disease. The lack of platelet destruction in these cases of acquired GT can be explained, either by the subclass of the autoantibodies (i.e. IgG2 or IgG4) or by the arrested platelet destruction by IgG1 (or IgG3) autoantibodies after splenectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 30 publications
1
22
0
1
Order By: Relevance
“…The inhibitory effect of aIIbb3 integrin autoantibodies on platelet aggregation is known for acquired Glanzmann thrombasthenia patients, with a primary coagulation defect in spite of (near) normal platelet counts. 35 This inhibitory effect exists in some immune thrombocytopenic purpura patients that, next to the thrombocytopenia, further impairs the primary coagulation. Clearly, this effect can be characterized by FCA.…”
Section: Fca Allows Testing the Effect Of Platelet Autoantibodies In mentioning
confidence: 99%
“…The inhibitory effect of aIIbb3 integrin autoantibodies on platelet aggregation is known for acquired Glanzmann thrombasthenia patients, with a primary coagulation defect in spite of (near) normal platelet counts. 35 This inhibitory effect exists in some immune thrombocytopenic purpura patients that, next to the thrombocytopenia, further impairs the primary coagulation. Clearly, this effect can be characterized by FCA.…”
Section: Fca Allows Testing the Effect Of Platelet Autoantibodies In mentioning
confidence: 99%
“…However, the patient's Abs recognized common recognition sites of PA anti‐αIIbβ3 autoAbs detected in chronic ITP patients, suggesting that the difference in epitope does not account for the unique phenotype of the patient's platelets. We identified that IgG subclasses of PA anti‐αIIbβ3 autoAbs of the patient were IgG1 and IgG2, which are usual in reported aGT cases . Because reduction of αIIbβ3 expression was not reported in these cases, it is also unlikely that the differences of IgG subclass affect the phenotype of our patient.…”
Section: Discussionmentioning
confidence: 51%
“…ii) Anti-CD20 (rituximab), has been successfully used in many autoimmune and alloimmune disorders. This may be an useful drug in acquired GT patients [46,47]. iii) Cytotoxic T lymphocyte antigen-4 (CTLA-4) antibody can be used for tolerance induction to prevent alloimmunization in GT [48].…”
Section: Expert Opinionmentioning
confidence: 99%